What can sector accounts tell about the financial crisis? - Gunther Gunther Tichy (Intereconomics, 2013)
The current sovereign debt crisis is widely believed to have been caused by insufficient budget discipline. However, the financial sector accounts reveal that public as well as private borrowing in the euro area was dwarfed by the synchronised explosion of assets and liabilities of financial corporations. The paper suggests that the current concentration on a speedy cutback of public debt is premature at best. Policy should pay more attention to the main causes of the crisis: the excesses of the financial sector and the flaws in the design of the heterogeneous currency union.
Keywords: 330